Chemical Study of Mordanting and Fixation Processes in Indigo, Sappanwood, and Tannin Natural Dyes Using Visual and UV-Vis Spectroscopic Analysis - Sayekti Wahyuningsih; Rahmawati Rahmawati; Djuminah Djuminah; Sri Murni; Nisaul Hasanah Abdul Rosyad; Teguh Endah Saraswati; Edi Pramono; Widyan Muhammad Naufal; Isna Nurmilatul Azizah; Rizqi Apriliyani; Nadia Octaviani Faiq Salsabila (G-Tech: Jurnal Teknologi Terapan, 2026)
Ecoprint is an eco-friendly textile dyeing technique whose color quality is strongly influenced by mordanting and fixation processes. However, inconsistent mordant–fixative systems often result in unstable color intensity and poor standardization. This study aimed to evaluate the effect of different mordant and fixative combinations on the color characteristics of ecoprint fabrics dyed with indigo (Indigofera tinctoria), sappanwood (Caesalpinia sappan), and tannin extracts. Cotton fabrics were treated with either conventional mordant or color mordant, followed by fixation using vinegar, bone lime, lime, clear ferrous sulphate, or ferrous sulphate. Color properties were analyzed using UV-Vis spectroscopy (200-800 nm) and RGB evaluation. Iron-containing mordant systems significantly enhanced absorbance intensity in the visible region. It reduced the RGB lightness values, indicating deeper, more stable colors. Indigo showed maximum absorption at 647-672 nm, with the darkest blue obtained with the color mordant combined with ferrous sulphate fixation. Sappanwood showed maximum absorbance in the 482-491 nm range, under iron-assisted treatments. Tannin dyeing produced the most pronounced darkening effect due to tannin–iron complex formation. Overall, iron-assisted mordant–fixative systems under controlled pH conditions provided the most optimal and reproducible color performance, offering a scientific basis for standardizing the ecoprint process in sustainable textile production.